Corporate governance and ownership: measurement and impact on corporate performance in Argentina - Bebczuk, Ricardo Néstor (2005)
The goal of this paper is twofold. First, we put together, for the first time, quantitative measures on the quality of the corporate governance and the ownership structure for 65 nonfinancial listed companies in Argentina with information for 2003-2004. A wide array of official and private sources were used to this purpose. In a nutshell, companies seem to be poorly governed vis-á -vis international practices. In turn, ownership appears to be quite concentrated at the level of the largest ultimate shareholder, but separation of control and cash flow rights prevails in less than half of the companies, with pyramiding being the main mechanism to create such wedge. Second, we put to the test the predictions of recent theories linking those measures with corporate performance in 2000-2003. Concerning performance, the results point to a sizable and robust effect of our governance measure on both the return on assets and Tobin’s q. Moreover, the separation of control and cash flow rights for the largest shareholder –an indicator of the incentives to expropriate minority shareholders- hinders performance directly, and also attenuates the beneficial impact from good governance rules.